Mechanism investigation on yellow phosphorus inducing O, O3 and OH• radicals in phosphate rock slurry for high-efficiency NO oxidation - Nie, Yunxiang; Xu, Lei; Yang, Yifan; He, Dedong; Mei, Yi (Separation and purification technology, 2023)
[Display omitted] •The O, O3 and OH• are generated by the reaction of P4 with O2.•The O and OH• play an extremely critical role in the efficient oxidation of NO.•The CaMg(CO3)2 and Ca5(PO4)3F efficiently improve denitrification efficiency.•NOx removal efficiency can reach above 90 %, when the molar ratio of O3/NO = 0.15.•The mechanism on oxidative removal of NO is speculated. NOx abatement with low cost is the difficulty for coal-fired flue gas at middle and low temperature. It is considered to be an extremely promising technology to eliminate NOx by employing phosphorus sludge and phosphate rock slurry as absorbent in the industry. However, due to the unclear denitrification mechanism, the consumption of phosphorus sludge is relatively large. Herein, the mechanism of NO oxidation and removal was investigated in depth, in the absorbent prepared by yellow phosphorus and phosphate rock slurry. The results show that the reaction of yellow phosphorus with oxygen in water can induce O atoms and OH• radicals, which are proved to be the major oxidants for the removal of NO, based on characterizations and theoretical calculation results. Hence, the denitrification efficiency is greater than 90%, when the molar ratio of O3 to NO is 0.15. Further, the possible reaction pathway for the oxidative removal of NO is proposed. Besides, magnesium calcium carbonate and calcium fluorophosphate, the main components of phosphate rock, play a crucial role in the efficient removal of NOx.